Uruk, Irak. Feldforschungen und Aufarbeitung von Grundlagenforschung // Konservierungsarbeiten in der Uruk-Warka-Sammlung des DAI an der Universität Heidelberg - van Ess, Margarete (e-Forschungsberichte des DAI, 2017)
Feldforschungen und Aufarbeitung von Grundlagendaten In summer 2016, Uruk (modern Warka) became part of the cultural and natural World Heritage “The Ahwar of Southern Iraq: refuge of biodiversity and the relict landscape of the Mesopotamian cities“. Fieldwork at Uruk was therefore composed of a scientific as well as a management/conservation component. It focused on surveying the suburbs of the ancient town, amending the topographic base through further geodetic and photographic documentation, developing conservation measures, as well as on some emergency conservation activities. All activities were interconnected with the training program “Iraqi-German Expert Forum on Cultural Heritage” (IGEF). At Uruk, for example, modules were offered on the techniques of archaeological fieldwork, the professional documentation and analysis of architectural remains, and on the development of conservation measures. The training components were generously funded by the German Foreign Office. Konservierungen in der Uruk-Warka-Sammlung des Deutschen Archäologischen Instituts an der Universität Heidelberg For the Uruk-Warka-Collection of small finds, stored and used as study collection at the University of Heidelberg, the programme for improvement of the magazines and the conservation of objects was continued in a close cooperation between the University of Heidelberg and the Orient-Department of the German Archaeological Institute.